Optimizing quality of care in patients admitted with chronic obstructive pulmonary disease exacerbation. (10th January 2022) - Tsao, Megan; Laikijrung, Chananid; Tran, Alan; Pon, Tiffany; Roach, Denise; Liu, Bo; Le, Kathie
Objectives : Adherence to Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines in acute exacerbation of chronic obstructive pulmonary disease (AECOPD) treatment is variable in the inpatient setting. This study evaluates appropriateness of therapy in patients admitted to an academic medical center for AECOPD.Methods : This was a single-center, retrospective, observational study. The primary endpoint was proportion of patients who received appropriate AECOPD treatment within 24 h. Secondary endpoints included mean length of stay (LOS) and time to administration (TTA) of pharmacotherapy, 30-day readmission rates, and proportions of various ancillary care received. Data were analyzed using descriptive and inferential statistics.Results : Of 533 screened admissions, 163 were included. Of those included, 55% ( n = 90) received guideline-based therapy within 24 h of presentation. This group had significantly shorter mean LOS (3.48 ± 2.61 vs 4.53 ± 3.40 days, p = .026), fewer COPD-related readmissions (7 vs 14, p = .036), and numerically fewer all-cause readmissions (14 vs 19, p = .11). Mean LOS and TTA were 3.95 ± 3.02 days and 8.47 ± 12.77 h, respectively.Discussion: Timely and guideline-based delivery of medications was associated with shorter length of stay and fewer COPD-related readmissions. Establishing a standardized care plan through order set implementation may be one strategy to improve care and outcomes in AECOPD patients.